Electronic structure and magnetic assets of FeCoGaO4 nanoparticles: An XANES investigation. (February 2022) - Sharma, Aditya; Varshney, Mayora; Kumar, Yogesh; Lee, Byeong-hyeon; Won, Sung Ok; Chae, Keun Hwa; Vij, Ankush; Sharma, Ram K.; Shin, Hyun-Joon
Abstract: In this study, FeCoGaO4 nanoparticles, which have rarely been reported, have been synthesized using a sonication-assisted hydrothermal method. X-ray diffraction (XRD) and transmission electron microscopy (TEM) results have revealed the formation of a single-phase compound with a particle size of 10–20 nm. X-ray absorption near-edge structure (XANES) investigations confirmed the presence of Fe 3+, Ga 3+ and Co 2+ ions in FeCoGaO4 . High saturation magnetization ( M s ) (∼50 emu/g), remanent magnetization ( M r ) (10 emu/g) and coercivity (∼630 Oe) are observed at 50 K. A lower coercivity (28 Oe), and M r (0.11 emu/g) are observed at 300 K. The origin of magnetism in the FeCoGaO4 nanoparticles has been mechanistically discussed considering the plausible magnetic interactions among the constituent ions in the material. Graphical abstract: Image 1 Highlights: Synthesis of FeCoGaO4 nanoparticles using a sonication-based chemical synthesis. The structure and morphology were investigated using XRD and HR-TEM. The electronic structure was determined using XANES at the O K-, Fe K-, Co K- and Ga K-edge spectra. The mechanistic of the magnetic properties have been revealed.